A test of a state-based, self-control theory of binge eating in adults with obesity. Issue 1 (2nd January 2018) - Pearson, Carolyn M.; Mason, Tyler B.; Cao, Li; Goldschmidt, Andrea B.; Lavender, Jason M.; Crosby, Ross D.; Crow, Scott J.; Engel, Scott G.; Wonderlich, Stephen A.; Peterson, Carol B.
ABSTRACT: It has been theorized that state the levels of self-control depletion (as caused by negative affect and restraint) may lead to binge eating (BE) when individuals also endorse momentary expectancies that eating will make them feel better (EE). Given commonalities in precipitants of BE across populations, the current study tested this theory in a sample of adults with obesity using ecological momentary assessment (EMA). Fifty obese adults completed the EMA protocol during which they provided pre-eating episode ratings of negative affect, restraint, and EE, and post-eating episode ratings of BE. Generalized estimating equations (GEE) identified a 3-way interaction between within-person pre-eating episode variables: higher self-control depletion (e.g., higher restraint and higher negative affect) was predictive of BE episodes only when individuals also endorsed higher EE. To our knowledge, this is the first empirical test of this theory, highlighting the impact of momentary self-control depletion and EE on BE in obese adults.